The Elitist Public Sphere In China: A Case Study Of Online Contestation By Former Critical Journalists During The Coronavirus Outbreak - Xiaojin, Sally (Javnost-The Public, 2022)
This paper explores a contingent sub-public sphere promoted by a group of former critical journalists in China during the coronavirus outbreak at the beginning of 2020. During the initial outbreak of coronavirus in China, the observed former journalists, who left the field of critical journalism during the re-structure of Chinese news industries under Xi Jinping’s leadership, drew on their knowledge of Chinese politics and censorship to contest information cover-up by the state, online censorship, and the state’s discourses of China as a successful model of combating the virus. Their activities effectively engaged mass participation of Chinese people and promoted critical opinions of the public. The paper bears the primary aim to deepen the understanding of the episodic formation of elite-driven public spheres in China by investigating the nuances of each case. I therefore, in this particular case study, explore concepts of habitus and capital from Bourdieu’s field theory as analytical tools in the investigation of the persistence of political participation and government scrutiny by former critical journalists on social media after leaving the field of critical journalism. The empirical research combines materials collected through 15 former critical journalists’ WeChat accounts between January and May 2020, along with in-depth interviews.